Biological dynamics of a Polish rural community in the XIX century: III. Description of the state of gene pool based on demographic data - Henneberg, Maciej (Anthropological Review, 1978)
The paper presents a part of the study undertaken within Biological History of Human Populations Research Program on the data derived from the registers of Szezepanowo parish (northern part of the Central Poland). In previous two papers Henneberg, 1977a and b] has been presented the general demographical characteristics of the parish together with analysis of marital migration and birth spacing. In the present paper are given estimations of the opportunity for selection and kinship. Opportunity for selection through differential mortality was measured with use of Ibs and Rpot indices (Henneberg and Piontek, 1975] as well as with Crow's Im index. The results obtained (see table 1) show that during nineteenth century opportunity for selection created by mortality was decrasing, being throughout the entire investigated period (1828 - 1874) on the level observed in European prehistoric populations. The opportunity for selection through differential fertility was measured with the use of author's Sf index. The index is calculated as a standard deviation of „reproductive abilities” (F) of women. The reproductive ability of a given woman is measured as an arithmetic mean of standarized (x -0, s—1), with respect to age and parliy, lenghts of prolo- and intergenctic intervals. This procedure is devised in order to reduce the share of „environmental” variance in the total variance of reproductive performance of women as measured in Crow's If index. After considering correlations between standarized durations of birth intervals of the same woman and some recalculations it was concluded that in the investigated group the share of genetic variance in S2 was very low (the rough estimate of heritability — h2 is less than 0.25). Therefore „useful” for operation of natural selection part of fertility variance is small – selection through fertility differenitals (disregarding cases of reproductive sterility) cannot be intense. The degree of changes in gene pool due to limited population size and constant exchange of mates over certian distance were measured with use of inbreeding coefficients. Coefficient of inbreeding estimated from isonymy is 0.0014 ± 0.0014 for the whole period studied. Estimates of f from data on migration population density and proportion of effective population size to the total population size (Ne : N) for successive decades and longer periods are given in the table 4. From the estimates of inbreeding in the investigated group it follows that the population cannot be considercd an „Isolałe”. Inhabitants of the region constituted a segment of large breeding population whose limits cannot be ascertained because of isotropic migration of considerable intensity, It noteworthy (see table 4) that with the passage of time the degree oi kinship in the investigated group decreases. Since during the period under study in this part of Poland considerable changes in technological and organisational conditions are occuring (shift from the last phase of feudalistic socio-economic structure toward free trade and enterprise one), interdependences between them and decreasing opportunity for selection together with declining degree of breeding isolation are worth consideration.